Microstructural evolution in bitaxial crack‐seal veins: A phase‐field study. Issue 5 (22nd May 2015) - Ankit, Kumar; Urai, Janos L.; Nestler, Britta
Abstract Bitaxial crack sealing by epitaxial crystal growth is the most common vein‐forming process in Earth's crust, but the details of the microstructural processes in these are not well understood. Here we model the evolution of bitaxial crack‐seal quartz veins in two and three dimensions, using the phase‐field method. Our numerical simulations show the influence of different parameters, such as the obliquity of crack opening and crack location, grain size, and orientations on the evolving vein microstructure. We examine the underlying growth competition observed during epitaxial growth of quartz. Results show many similarities with natural microstructures such as stretched crystals and compare well with the previous numerical findings. As the ratio of crack aperture and matrix grain size for the present studies is chosen to be sufficiently large for growth competition to occur before complete sealing, it leads to the formation of crystal fragments along the crack‐opening trajectory. We explain how such fragment trails act as potential indicators of the opening of crack‐seal veins, if they are confirmed to be common in natural microstructures. Finally, we highlight the importance of accounting for the third dimension in the numerical simulations by analyzing the evolution of fluid connectivity in 2‐D and 3‐D during the sealing process.